Ultrafiltration rate is an important determinant of microcirculatory alterations during chronic renal replacement therapy - Veenstra, Gerke; Pranskunas, Andrius; Skarupskiene, Inga; Pilvinis, Vidas; Hemmelder, Marc H.; Ince, Can; Boerma, E. Christiaan (BMC nephrology, 2017)
Hemodialysis (HD) with ultrafiltration (UF) in chronic renal replacement therapy is associated with hemodynamic instability, morbidity and mortality. Sublingual Sidestream Dark Field (SDF) imaging during HD revealed reductions in microcirculatory blood flow (MFI). This study aims to determine underlying mechanisms. The study was performed in the Medical Centre Leeuwarden and the Lithuanian University of Health Sciences. Patients underwent 4-h HD session with linear UF. Nine patients were subject to combinations of HD and UF: 4 h of HD followed by 1 h isolated UF and 4 h HD with blood-volume-monitoring based UF. Primary endpoint: difference in MFI before and after intervention. During all sessions monitoring included blood pressure, heartrate and SDF-imaging. NCT01396980. Baseline characteristics were not different between the two centres as within the HD/UF modalities. MFI was not different before and after HD with UF. Total UF did not differ between modalities. Median MFI decreased significantly during isolated UF [2.8 (2.5-2.9) to 2.5 (2.2-2.8), p = 0.03]. Baseline MFI of each UF session was correlated with MFI after the intervention (r = 0.52, p = 0.006). During HD with UF or isolated HD we observed no changes in MFI. This indicates that non-flow mediated mechanisms are of unimportance. During isolated UF we observed a reduction in MFI in conjunction with a negative intravascular fluid balance. The correlation between MFI before and after intervention suggests that volume status at baseline is a factor in microvascular alterations. In conclusion we observed a significant decrease of sublingual MFI, related to UF rate during chronic renal replacement therapy.